Long non-coding RNAs: emerging functional players in the pathobiology and progression of myeloid leukemia - Dutta, Sangeeta; Akhade, Vijay Suresh; Choudhury, Subhendu Roy; Rao, Manchanahalli Rangaswamy Satyanarayana (Frontiers in RNA Research, 2024)
Advancement and innovation in transcriptomics and computational biology have revealed long noncoding RNAs as major regulators of essential biological processes. Their restricted spatial and temporal expression, along with their ability to interact with nucleic acids (DNA and RNA) as well as proteins, makes them key players in chromosome integrity, genomic architecture, transcriptional and post-transcriptional regulation. Their dysregulation has been associated with numerous diseases and pathological conditions including cancers. Myeloid leukemia, a malignancy of the hematopoietic system, is no exception and the number of lncRNAs with functional significance in its pathobiology is rapidly increasing. In this comprehensive review, we have summarized the majority of the reported lncRNAs in Acute myeloid leukemia (AML) and Chronic myeloid leukemia (CML), focusing on regulatory mechanisms by which they modulate the progression and pathogenesis of the disease, their potential as diagnostics and prognostic markers and how they can serve as novel therapeutic targets. We have also highlighted our recent work on the significance of lncRNA Hmrhl in CML, which was found to regulate gene transcription at the chromatin level.